EVALUASI PENGARUH RAMBU TERHADAP KESELAMATAN LALU LINTAS (Studi Kasus Jalan Jogja-Wonosari Km.17-Km.24 Kabupaten Gunung Kidul Daerah Istimewa Yogyakarta) - Lako Gowa, Fransiskua Xaverius; Handayani, Ani Tjitra (ReTII, 2022)
There are many factors that affect traffic safety, one of which is road signs. Road signs provide information such as warnings, prohibitions, orders and instructions for road users to create smooth, orderly and safe driving. The location and number of road signs will cause a problem if it is not calculated properly and has an impact on the safety of road users. The purpose of this study was to determine the relationship between the influence of road signs on traffic safety, completeness of guava facilities, accident rates, and solutions to minimize the problem of traffic accidents that occurred in Gunung Kidul Jl. Jogja – Wonosari, Kec. Patuk km 17 – km 24. The calculation of the data in this study uses the IPA (Importance Performance Analysis) method to process primary data derived from questionnaires and descriptive analysis to process secondary data in the form of accident data in 2016-2018 obtained from relevant agencies. Based on the results of the analysis of the effect of signs on traffic safety in Kab. Gunung Kidul, Jalan Jogja – Wonosari, Kec. Patuk Km.17-Km.24, obtained a performance suitability level of 100.01%. The existing road sign facilities at Gunung Kidul jln. Jogja – Wonosari, Kec. Patuk km 17 – km 24 as many as 144 with the highest accident rate occurring at km 19-km 20 as many as 14 cases. So it is necessary to do socialization regarding order in driving and repair of damaged road signs.